The transfer of a European company's in-house abstracting service to the Philippines a case study of its growth and development - Sonido, Ernesto G.; Quiros, Edgardo B.; Faderon, Rosalie B. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2003)
This case study observes the transfer of an in-house abstracting service of European company to the Philippines. It looks at the reasons behind the transfer and the developmental stages of the transfer. In particular, the study attempts to look at the issues, challenges and solutions formulated for the completion of the transfer.
It took eighteen months for the transfer to be completed. The first phase involved the preparation of the transfer: the installation, testing and formulation of back plans for groupware, computer hardware and Internet connections; the setting up of the team's organization and recruitment of local abstractors; the appointment and posting of a copy editor to Manila; and the training of the team's managing editor in Europe. The second phase involved the training of the abstractors. The training period took around twelve months. It was reported that the main hindrance in the abstracting operations was the cultural misunderstanding of the abstractors. This was corrected by conducting seminars and activities aimed at familiarizing the culture of the publication being abstracted. During that time nearly all abstractors were regularized. This meant that they had attained the level of competence required by the copy editor. However, despite this, there was the inconsistency problem with regards to the quality of the abstracting teams work. This problem was corrected in the third stage with the implementation of a quality audit program. A month after the implementation of the program, the drop in the quality scores was arrested and the quality figures and production figures began to go up. A few months after, February 2002, the transfer of the in-house English abstracting services was completed.
The company decided to transfer its operations here because of lower labor costs, the abstractors' high level of education, advantage of time difference between Europe and the Philippines. The company also decided to set-up the in-house service rather than out-sourcing it because it already had an existing subsidiary company here and an in-house service would be more sensitive to the needs of the company. An additional advantage with an in-house service would be that sensitive company information, if any, would not be given to another company.
The critical areas of the transfer were the preparation and testing of the infrastructure (communication, software and hardware component.), the organization and recruitment of the team, the training and the implementation of quality audit and action plan be implemented soon after.
Vita.
Thesis (Master of Library and Information Science)
Keywords: Abstracting and indexing services -- Philippines